EFFECT OF ORGANIC AND INORGANIC FERTILIZER DOSES ON YIELD AND YIELD COMPONENTS OF COMMON BEANS - Murat TUNC; Sibel Ipekesen; Fatma BASDEMIR; Cuma AKINCI; Behiye Tuba BICER (Journal of Animal and Plant Sciences, 2023)
An experiment was carried out at the Dicle University, Agriculture Faculty, southeast Anatolia of Turkey during the years 2020 and 2021. The study was conducted to determine the effect of chicken manure levels (2.0 and 3.0 t ha-1), nitrogen and phosphorus levels (40:60, 40:80 and 40:100 kg ha-1) and their combinations (chicken manure levels + NP levels) on the growth, yield and yield components of common beans (Phaseolus vulgaris L.) The experiment was laid out in a randomized complete block design with three replications. Fertilizers on the soil surface were applied at sowing time. Dry biomass, dry stem weight, dry leaf weight and leaf area were investigated at 15 days intervals starting from 20 days after the emerging (DAE) until 80 DAE.Seed yield and yield components were evaluated at the maturity time. The effect of fertilizer treatments on growth, yield and yield components was significant, and fertilizer treatments increased the growth, yield and yield components compared to the control. The highest dry biomass, dry stem weight, dry leaf weight and leaf area values were observed when chicken manure 3 t ha-1 +40N+100P kg ha-1 at 65 DAE was applied. The highest seed yield, number of primary and secondary branches and pod weight plant-1 were observed at the application of chicken manure 2 t ha-1 + 40N + 60P kg ha-1 combination. Seed yield ranged from 1521.5 kg ha-1 in control plots to 2742.1 kg ha-1 in chicken 2 t ha-1 + 40N + 100P kg ha-1. Therefore, adding chicken manure (2 t ha-1) and chemical fertilizers (40N+100P kg ha-1) combinations to nutrient management systems was deduced more efficient than chemical fertilizer or chicken manure alone treatments on growth and yield of common bean.
Keywords: Chicken manure; Common bean; Chemical fertilizer; Turkey; Yield; Yield components